Meningkatkan Hasil Belajar dan Motivasi Peserta Didik dalam Pembelajaran Matematika dengan Media Quizizz dan Pendekatan Teaching at the Right Level (TaRL) - Januari, Ni Komang Januari; Novitasari, Dwi; Astuti, Yuli (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to improve students’ learning outcomes and motivation in mathematics through the use of Quizizz media and the Teaching at the Right Level (TaRL) approach. The study was conducted in class X-7 of SMAN 6 Mataram with 34 students. Based on the initial assessment, many students experienced difficulties in understanding problems and showed low learning motivation. To address these issues, the Problem-Based Learning (PBL) model was implemented using the TaRL approach, supported by interactive media such as Quizizz, student worksheets (LKPD), and instructional videos. The results showed a significant improvement in both students’ learning outcomes and motivation. The average score increased from 65 to 82, with the percentage of students achieving scores above the minimum mastery criterion (KKM) rising from 40% to 85%. Moreover, students’ learning motivation improved, as evidenced by their active participation in discussions and enthusiasm in completing tasks through Quizizz. The TaRL approach helped students understand the material according to their individual learning levels, while Quizizz made the learning process more engaging and interactive. Thus, the combination of differentiated instruction and interactive digital media proved effective in enhancing students’ learning outcomes and motivation.